Oxysterol Binding Protein: Tether, Transporter… and Flux Capacitor?. Issue 7 (July 2019) - Hammond, Gerald R.V.; Pacheco, Jonathan
Abstract : The oxysterol binding protein (OSBP) is a storied protein in organelle biology. Its early roles include acting as a membrane contact site (MCS) tether as well as a lipid antiporter. A surprising new function for OSBP in MCS dynamics has now been uncovered in a recent study by Jamecna et al. ( Dev. Cell 2019;49:220–234).